Power of song : an analysis on the power of music festivals or conserts as a tool for human rights education in Africa - Cistac, Doutor Gilles (University of Pretoria, 2011)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2010.